2022
DOI: 10.1002/tox.23641
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum and cadmium co‐exposure promotesM1macrophage polarization through oxidative stress‐mediated inflammatory response and induces pulmonary fibrosis inShaoxing ducks (Anas platyrhyncha)

Abstract: High molybdenum (Mo) and cadmium (Cd) are harmful to the body, but pulmonary toxicity induced by Mo and Cd co‐exposure is unknown. To assess the combined impacts of Mo and Cd on fibrosis through M1 polarization in the lung of ducks, 80 healthy 8‐day‐old Shaoxing ducks (Anas platyrhyncha) were randomly assigned to 4 groups and fed with containing unequal doses of Mo or/and Cd diet. Lung tissues were collected on the 16th week. Results indicated that Mo or/and Cd significantly increased their contents in the lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…TPHP has been considered to be related to chronic inflammatory diseases, such as obesity through lipid metabolism disorders, inducing the formation of foam cells, promoting the development of atherosclerosis 30 . Macrophages usually play a key role in these diseases, which means that TPHP may also have toxic effects on immune cells 31,32 . In order to verify underlying immune toxicity of TPHP and its association with immune diseases, RAW 264.7 cells were used in this study, which is one of the important models representing the in vitro evaluation of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPHP has been considered to be related to chronic inflammatory diseases, such as obesity through lipid metabolism disorders, inducing the formation of foam cells, promoting the development of atherosclerosis 30 . Macrophages usually play a key role in these diseases, which means that TPHP may also have toxic effects on immune cells 31,32 . In order to verify underlying immune toxicity of TPHP and its association with immune diseases, RAW 264.7 cells were used in this study, which is one of the important models representing the in vitro evaluation of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…30 Macrophages usually play a key role in these diseases, which means that TPHP may also have toxic effects on immune cells. 31,32 In order to verify underlying immune toxicity of TPHP and its association with immune diseases, RAW 264.7 cells were used in this study, which is one of the important models representing the in vitro evaluation of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…increase malondialdehyde (MDA) content, and then aggravate occurrence of lipid peroxidation (LPO) in the body, ultimately causing damage to organisms. 10 Hence, the biological toxicity of excess Mo has been widely concerned by many researchers. Environmental Mo and Cd levels are rapidly increasing due to industrial production and human activities.…”
Section: Introductionmentioning
confidence: 99%
“…The kidney, testicle, ovary, and heart are the primary organs damaged by Mo toxicity 8,9 . Study has shown that high concentrations of Mo can significantly reduce glutathione peroxidase (GSH‐px) and glutathione (GSH) activities and increase malondialdehyde (MDA) content, and then aggravate occurrence of lipid peroxidation (LPO) in the body, ultimately causing damage to organisms 10 . Hence, the biological toxicity of excess Mo has been widely concerned by many researchers.…”
Section: Introductionmentioning
confidence: 99%